Etika dalam Literasi Media Sosial: Panduan untuk Pengguna yang Bertanggung Jawab - Nasution, Indah Widya Jaya Putri; Nasution, Muhammad Irwan Padli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Technological developments are increasingly rapid, which means that the flow of information can be obtained from various social media. However, not all groups of people are able to use social media well, due to the lack of literacy ethics when using social media, there are many misuses of social media, such as committing fraud, hoax news which can harm many people. Therefore, the aim of this research is to find out what ethics are in good social media literacy so that it can be a guide to being more responsible in using social media. This research uses library research which is analyzed using a descriptive analysis approach. The results of this research are that when using social media, the ethical principles that must be applied are; honesty and credibility, respect for privacy, respect for diversity and inclusion, digital awareness and communication ethics.